Exploring the Kamal Transform: Properties, Applications, and Extension to Integrable Boehmians - A. J. Ghanwat (Mathematics and Computer Science: Contemporary Developments Vol. 7, 2024)
The present article incorporates some of the properties of the Kamal transform which is derived from classical Fourier integral, a few examples and the applications of Kamal transform for solving initial value problems where the initial conditions are not specified to obtain the general solution of differential equations. Moreover, the Kamal transform on Integrable Boehmians is developed along with the demonstration of its basic properties.